2010
DOI: 10.1108/14676371011031838
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in higher education in the Asia‐Pacific: developments, challenges, and prospects

Abstract: Purpose-The purpose of this paper is to provide an overview of the contributions of the Asia-Pacific region to leading practice in sustainability in higher education (HE), as prelude and orientation to this special issue collection from different countries and regions. Design/methodology/approach-This is a critical review that includes international and regional policy contexts in sustainability and "education for sustainable development" (ESD), whilst exploring the trajectories of key initiatives across the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(94 citation statements)
references
References 15 publications
(15 reference statements)
1
74
0
6
Order By: Relevance
“…For example, an examination of PSE operational policies throughout this region reveals the strong role government policies have in spurring the development of institutional policies in nations, such as Australia, China, Japan and the Philippines [39]. However, while many individual institutions in these countries are implementing new sustainable operations policy initiatives, a recent overview of the region has found that despite a high level of government support for sustainability initiatives in PSE operations, there is an insufficient level of collaboration among PSE institutions in the region compared to PSE sustainability networks in other regions [23].…”
Section: Comparing Campus Operations Policiesmentioning
confidence: 99%
“…For example, an examination of PSE operational policies throughout this region reveals the strong role government policies have in spurring the development of institutional policies in nations, such as Australia, China, Japan and the Philippines [39]. However, while many individual institutions in these countries are implementing new sustainable operations policy initiatives, a recent overview of the region has found that despite a high level of government support for sustainability initiatives in PSE operations, there is an insufficient level of collaboration among PSE institutions in the region compared to PSE sustainability networks in other regions [23].…”
Section: Comparing Campus Operations Policiesmentioning
confidence: 99%
“…The declaration of the United Nations Decade on Education for Sustainable Development (UNDESD) 2005-2014 represented a lever for the integration of sustainability in all sectors of education across the globe. Several papers and publications have reviewed the policy context and contributions that different countries and regions are making to the UNDESD [4][5][6]. The UNDESD has encouraged and offered leadership, recommendations and guidelines to embed the principles of education for sustainable development (ESD) within educational policy and programs.…”
Section: Introductionmentioning
confidence: 99%
“…At the global level, over one thousand university presidents and vice-chancellors have signed the sustainability-related declaration, committing their institutions to change towards sustainability. A detailed description and chronology of the sustainability declarations signed by the university presidents is provided in Chapter 2. International declarations may provide useful publicity to encourage progress of ESD (Ryan et al, 2010). According to L4, University A's endeavour to compete at the global level and to internationalise its program and contribution has driven the ESD initiative in University A, as sustainability is becoming increasingly pertinent to global higher education (Levy, 2012;Sterling, 2004;Tilbury, 2004).…”
Section: Global Influence On Esd In University Amentioning
confidence: 99%